Distributive justice and police legitimacy: the demographic and geographical distribution of police ID checks in Spain - López-Riba,José María (Universidad de Talca, 2021)
Abstract The distribution of police activity throughout society is a key issue for distributive justice and police legitimacy. This article presents two studies on the distribution of police identification checks in Catalonia (Spain) using data provided by Mossos d’Esquadra (the Catalan Regional Police). The first study explores the demographic distribution of ID checks, in other words, which groups of people are more likely to be stopped and have their identification checked by police. The second study examines the geographical distribution, that is, in which places are there greater concentrations of ID checks. The results show that with regards to demographics, men, young people and foreign people are associated with higher levels of ID checks. In addition, the geographical distribution is not primarily driven by crime rates, thus, in general, it seems that the distribution of ID checks is not as strongly related to crime as may be expected.